2019
DOI: 10.1177/0300060519856155
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbilirubinemia as a predictor of severity of acute appendicitis

Abstract: Objective This study aimed to investigate the clinical significance of preoperative hyperbilirubinemia in Japanese patients and to assess its clinical potential as a predictor of the severity of acute appendicitis. Methods We studied 318 patients with appendicitis who underwent appendectomy between July 2010 and June 2017. We analyzed preoperative data including age, sex, white blood cell count, C-reactive protein (CRP) level, fever, peritoneal irritation signs, and serum total bilirubin level as potential ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 16 publications
4
17
0
Order By: Relevance
“…Given that the study conducted by Chaudhary et al involved only eight patients with complicated appendicitis and that all of whom had hyperbilirubinemia, the observed high diagnostic efficacy was expected. Recently, Iftikhar et al reported hyperbilirubinemia as a predictor for complicated appendicitis, with a sensitivity of 56.60% and a specificity of 95.45% [ 27 ]. Other recent studies also reported that elevated TBIL levels are associated with later stages of appendicitis [ 13 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that the study conducted by Chaudhary et al involved only eight patients with complicated appendicitis and that all of whom had hyperbilirubinemia, the observed high diagnostic efficacy was expected. Recently, Iftikhar et al reported hyperbilirubinemia as a predictor for complicated appendicitis, with a sensitivity of 56.60% and a specificity of 95.45% [ 27 ]. Other recent studies also reported that elevated TBIL levels are associated with later stages of appendicitis [ 13 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings suggest that there is a relationship between increased TSB level and acute appendicitis and its complications (20,21) . The risk of perforation increases threefold in patients with TSB levels higher than 1 mg/dL (12) .…”
Section: Discussionmentioning
confidence: 86%
“…Studies have found that Escherichia coli endotoxin can cause dose-dependent cholestasis, and Escherichia coli can also cause hemolysis of red blood cells, thereby increasing the bilirubin load ( 24 , 25 ). Furthermore, in CA patients, severe inflammation can lead to intestinal edema and hypomotility, which can also lead to cholestasis ( 26 ). Sevinç MM et al found that TBil >1.0 mg/dL was significantly associated with appendix perforation (OR = 2.6) in 3392 patients with acute appendicitis ( 27 ).…”
Section: Discussionmentioning
confidence: 99%